A novel hydrogen peroxide evolved CHO host can improve the expression of difficult to express bispecific antibodies - Mistry,RK; Kelsall,E; Sou,SN; Barker,H; Jenns,M; Willis,K; Zurlo,F; Hatton,D; Gibson,SJ (Biotechnology and Bioengineering, 2021)
Abstract The manufacture of bispecific antibodies by Chinese hamster ovary (CHO) cells is often hindered by lower product yields compared to monoclonal antibodies. Recently, reactive oxygen species have been shown to negatively impact antibody production. By contrast, strategies to boost cellular antioxidant capacity appear to be beneficial for recombinant protein expression. With this in mind, we generated a novel hydrogen peroxide evolved host using directed host cell evolution. Here we demonstrate that this host has heritable resistance to hydrogen peroxide over many generations, displays enhanced antioxidant capacity through the upregulation of several, diverse antioxidant defense genes such as those involved in glutathione synthesis and turnover, and has improved glutathione content. Additionally, we show that this host has significantly improved transfection recovery times, improved growth and viability properties in a fedbatch production process, and elevated expression of two industrially relevant difficult to express bispecific antibodies compared to unevolved CHO control host cells. These findings demonstrate that host cell evolution represents a powerful methodology for improving specific host cell characteristics that can positively impact the expression of difficult to express biotherapeutics.